Safety and immunogenicity of a recombinant live attenuated tetravalent dengue vaccine (DENVax) in fl avivirus-naive healthy adults in Colombia: a randomised, placebo-controlled, phase 1 study (2014)
ABSTRACT: Background Dengue virus is the most serious mosquito-borne viral threat to public health and no vaccines or antiviral therapies are approved for dengue fever. The tetravalent DENVax vaccine contains a molecularly characterised live attenuated dengue serotype-2 virus (DENVax-2) and three recombinant vaccine viruses expressing the prM and Estructural genes for serotypes 1, 3, and 4 in the DENVax-2 genetic backbone. We aimed to assess the safety and immunogenicity of tetravalent DENVax formulations. Methods We undertook a randomised, double-blind, phase 1, dose-escalation trial between Oct 11, 2011, and Nov 9, 2011, in the Rionegro, Antioquia, Colombia. The fi rst cohort of participants (aged 18–45 years) were randomly assigned centrally, via block randomisation, to receive a low-dose formulation of DENvax, or placebo, by either subcutaneous or intradermal administration. After a safety assessment, participants were randomly assigned to receive a high-dose DENVax formulation, or placebo, by subcutaneous or intradermal administration. Group assignment was not masked from study pharmacists, but allocation was concealed from participants, nurses, and investigators. Primary endpoints were frequency and severity of injection-site and systemic reactions within 28 days of each vaccination. Secondary endpoints were the immunogenicity of DENVax against all four dengue virus serotypes, and the viraemia due to each of the four vaccine components after immunisation. Analysis was by intention to treat for safety and per protocol for immunogenicity. Because of the small sample size, no detailed comparison of adverse event rates were warranted. The trial is registered with ClinicalTrials.gov, number NCT01224639. Findings We randomly assigned 96 patients to one of the four study groups: 40 participants (42%) received low-dose vaccine and eight participants (8%) received placebo in the low-dose groups; 39 participants (41%) received high-dose vaccine, with nine (9%) participants assigned to receive placebo. Both formulations were well tolerated with mostly mild and transient local or systemic reactions. No clinically meaningful diff erences were recorded in the overall incidence of local and systemic adverse events between patients in the vaccine and placebo groups; 68 (86%) of 79 participants in the vaccine groups had solicited systemic adverse events compared with 13 (76%) of 17 of those in the placebo groups. By contrast, 67 participants (85%) in the vaccine group had local solicited reactions compared with fi ve (29%) participants in the placebo group. Immunisation with either high-dose or low-dose DENVax formulations induced neutralising antibody responses to all four dengue virus serotypes; 30 days after the second dose, 47 (62%) of 76 participants given vaccine seroconverted to all four serotypes and 73 (96%) participants seroconverted to three or more dengue viruses. Infectious DENVax viruses were detected in only ten (25%) of 40 participants in the low-dose group and 13 (33%) of 39 participants in the high-dose group. Interpretation Our fi ndings emphasise the acceptable tolerability and immunogenicity of the tetravalent DENVax formulations in healthy, fl avivirus-naive adults. Further clinical testing of DENVax in diff erent age groups and in dengue-endemic areas is warranted. Funding Takeda Vaccines.